Diagnostic delay in clinical practice: A case report of Coeliac disease (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Once considered a gastrointestinal disease of childhood affecting mainly whites, Coeliac Disease is now recognized as a systemic disease that may affect persons of any age and many races and ethnic groups. In this paper we present a case of a 60-year-old woman presented with protein-losing enteropathy associated with partial villous atrophy on distal duodenal biopsy. In Coeliac enteropathy the changes in intestinal permeability is sufficient to cause excessive loss of protein into the gut leading to hypoproteinaemia. The patient had presented with peripheral oedema without liver or renal impairment. The case emphasizes that clinicians should have a heightened suspicion about the disease that may be present at any age in both sexes and in a wide variety of clinical circumstances.